1999
DOI: 10.1002/(sici)1097-0215(19990105)80:1<134::aid-ijc24>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of a xenografted human colonic carcinoma using cisplatin or doxorubicin encapsulated in long-circulating pegylated stealth liposomes

Abstract: We compared the therapeutic effects of low doses of cisplatin and doxorubicin hydrochloride encapsulated in long‐circulating liposomes composed of cholesterol/hydrogenated soy phosphatidylcholine‐polyethylene glycol‐distearoyl‐phosphatidyl‐ethanolamine. The encapsulation of cisplatin and doxorubicin in these liposomes made ineffectively low doses of the free drugs able to inhibit the growth of and affect cures of a human colonic carcinoma growing in nude mice. Liposome‐encapsulated cisplatin had minor systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 14 publications
(23 reference statements)
2
14
0
Order By: Relevance
“…Comparisons were made to see if 1) plasma concentrations of BAM are increased and the systemic circulation time is prolonged for BAM-L; 2) the systemic clearance is reduced and 3) the tissue distribution is increased, especially in liver and spleen. Previously, studies confirming the above observations have been conducted on the liposomal formulations of antineoplastic drugs, including vincristine (Vaage et al, 1995), doxorubicin (Vaage et al, 1999) and taxol (Sharma and Straubinger, 1994). These studies demonstrated that these antineoplastic drugs encapsulated in liposomes increased the efficacy and reduced the toxicity in non-target tissue.…”
Section: Plasma Pharmacokinetics and Tissue Distribution Studymentioning
confidence: 60%
“…Comparisons were made to see if 1) plasma concentrations of BAM are increased and the systemic circulation time is prolonged for BAM-L; 2) the systemic clearance is reduced and 3) the tissue distribution is increased, especially in liver and spleen. Previously, studies confirming the above observations have been conducted on the liposomal formulations of antineoplastic drugs, including vincristine (Vaage et al, 1995), doxorubicin (Vaage et al, 1999) and taxol (Sharma and Straubinger, 1994). These studies demonstrated that these antineoplastic drugs encapsulated in liposomes increased the efficacy and reduced the toxicity in non-target tissue.…”
Section: Plasma Pharmacokinetics and Tissue Distribution Studymentioning
confidence: 60%
“…Studies have been performed with vincristine (Allen et al 1995 ;Vaage et al 1993a), mitoxantrone (Chang et al 1997) and platinum analogues (Mori et al 1996 ;Newman et al 1999 ;Vaage et al 1999 ;Harrington et al 2000c). In the case of vincristine and mitoxantrone, liposomal encapsulation was shown to signi® cantly increase their antitumour activity, while, for vincristine, reducing the toxicity of treatment.…”
Section: Sterically Stabilized Liposomesmentioning
confidence: 99%
“…Long-circulating polyethyleneglycol(PEG)-coated liposomes may therefore represent an attractive alternative. The therapeutic efficacy of various anticancer drugs was found to be increased by increasing the circulation times of the drug in blood when encapsulated in PEG-liposomes (Allen et al 1991, Vaage et al 1999.…”
Section: Introductionmentioning
confidence: 99%